Pengaruh E-Flashcard terhadap Perilaku Remaja Putri dalam Hygiene Genitalia saat Menstruasi - Sabrina, Mayang; Wardani, Sri Wisnu; Widayani, Wiwin; Ferina, Ferina (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2025)
Background: Genital hygiene during menstruation is crucial for preventing reproductive health issues. Low literacy among adolescent girls regarding genital hygiene increases infection risk due to improper practices. E-flashcards, as interactive digital media, have proven effective in enhancing learning motivation and comprehension, offering accessible education anytime and anywhere. This study aims to analyze the impact of e-flashcard media on adolescent girls' genital hygiene behavior during menstruation Method: The research method used a quasi-experimental design with a non-equivalent control group pretest-posttest design approach. The sample amounted to 124 female students, selected using one-stage cluster sampling, divided into experimental and control groups, data analysis using the T test. Result: The results showed that the average age of adolescents was 13-14 years old and had received information on genital hygiene during menstruation. In the experimental and control groups there was a significant increase in behavior with a p value <0.05. It can be concluded that e-flashcards effectively improve the behavior of adolescent girls in maintaining genital hygiene during menstruation Implication: e-flashcard is recomended as a media for reproductive health particularly in improving genital hygiene behavior during menstruation to prevent reproduktive health problems Novelty: This study has presented media innovation in digital platform designed directly by form in accordance with the pillars of health transformation